ARIA 2016: Resumen ejecutivo vías de atención integradas para una medicina preventiva a lo largo del ciclo vital - Guzmán M., María Antonieta; Calvo, Mario; Abusada A., Nancy; Afani S., Alejandro; Álvarez, Emilio; Caro, Jorge; Pérez, Tamara; Ruiz C., Mauricio; Sepúlveda C., Cecilia; Valdés A., Felipe; Agache, Ioana; Bachert, Claus Bachert; et al. (Revista Hospital Clínico Universidad de Chile, 2017)
The Allergic Rhinitis and its Impact on Asthma (ARIA) initiative commenced during a World Health Organization (WHO) workshop in 1999. The initial goals were (i) to propose a new allergic rhinitis classification, (ii) to promote the concept of multi-morbidity in asthma and rhinitis and (iii) to develop guidelines with all stakeholders for global use in all countries and populations. ARIA - disseminated and implemented in over 70 countries globally - is now focusing on the implementation of emerging technologies for individualized and predictive medicine. MASK (MACVIA (Contre les MAladies Chroniques pour un VIeillissement Actif)-ARIA Sentinel NetworK) uses mobile technology to develop care pathways in order to enable the management of rhinitis and asthma by a multi-disciplinary group or by patients themselves. An App (Android and iOS) is available in 20 countries and 15 languages. It uses a visual analogue scale to assess symptom control and work productivity as well as a clinical decision support system. It is associated with an inter-operable tablet for physicians and other health care professionals. The scaling up strategy uses the recommendations of the European Innovation Partnership on Active and Healthy Ageing.